Advancing Roles and Therapeutic Potentials of Pyroptosis in Host Immune Defenses against Tuberculosis - Jiayi Yang; Yuhe Ma; Jiaqi Yu; Yilin Liu; Jiaojiao Xia; Xinen Kong; Xiaoying Jin; Jiaxiang Li; Siqi Lin; Yongdui Ruan; Fen Yang; Jiang Pi (Biomolecules)
Tuberculosis (TB), an infectious disease caused by Mycobacterium tuberculosis (Mtb) infection, remains a deadly global public health burden. The use of recommended drug combinations in clinic has seen an increasing prevalence of drug-resistant TB, adding to the impediments to global control of TB. Therefore, control of TB and drug-resistant TB has become one of the most pressing issues in global public health, which urges the exploration of potential therapeutic targets in TB and drug-resistant TB. Pyroptosis, a form of programmed cell death characterized by cell swelling and rupture, release of cellular contents and inflammatory responses, has been found to promote pathogen clearance and adopt crucial roles in the control of bacterial infections. It has been demonstrated that Mtb can cause host cell pyroptosis, and these host cells, which are infected by Mtb, can kill Mtb accompanied by pyroptosis, while, at the same time, pyroptosis can also release intracellular Mtb, which may potentially worsen the infection by exacerbating the inflammation. Here, we describe the main pathways of pyroptosis during Mtb infection and summarize the identified effectors of Mtb that regulate pyroptosis to achieve immune evasion. Moreover, we also discuss the potentials of pyroptosis to serve as an anti-TB therapeutic target, with the aim of providing new ideas for the development of TB treatments.